1987
DOI: 10.1080/15298668791385507
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Relationship Between Airborne Contaminants and Environmental Factors in Dutch Swine Confinement Buildings

Abstract: A total of 171 swine confinement buildings were studied to determine the concentrations of airborne total and D50 less than or equal to micron 8.5 dust fractions, total and gram-negative bacteria, bacterial endotoxin and NH3. The concentrations of these airborne contaminants then were correlated statistically to a number of environmental factors such as feeding practices, number of animals and ventilation parameters. The results showed that airborne dust, endotoxin, bacteria and NH3 are commonly in high concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
3

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 0 publications
5
59
3
Order By: Relevance
“…This is in accordance with the association found between automated feeding systems and chronic symptoms in our former study [49] and with the slightly lower lung function for farmers with automated systems found in that study and earlier by Bongers and co workers [9]. In another part of our study [37] we showed that wet feeding is associated with lower exposure to dust, as reported also by Attwood and coworkers [2]. Both in this and former studies, there is evidence that the combination of automation with dry feed is associated with adverse health effects.…”
Section: Discussionsupporting
confidence: 93%
“…This is in accordance with the association found between automated feeding systems and chronic symptoms in our former study [49] and with the slightly lower lung function for farmers with automated systems found in that study and earlier by Bongers and co workers [9]. In another part of our study [37] we showed that wet feeding is associated with lower exposure to dust, as reported also by Attwood and coworkers [2]. Both in this and former studies, there is evidence that the combination of automation with dry feed is associated with adverse health effects.…”
Section: Discussionsupporting
confidence: 93%
“…For the measurement of both viable fungi and endotoxins this problem has been discussed in the literature recently (17,18,30,31). However the measurements of viable fungi and endotoxins performed by our laboratory in other occupational settings, such as swine confinement buildings and grain elevators , are clearly in concordance with the results of other published studies and are not suggestive of a serious underestimation of exposure levels (18,19,32,33). The use of glass fiber filters instead of absolute filters might be a factor which could have contributed to an underestimation of the endotoxin exposure in this specific low-exposure situation.…”
Section: Discussionsupporting
confidence: 81%
“…The analyses were done . in our laboratory according to a previously described procedure (19), using the Coatest Endotoxin Test Kit (Kabivitrum, Sweden). The filter extract was split into two fractions and spiked with a known quantity of endotoxin delivered with the test kit.…”
Section: Mlsmentioning
confidence: 99%
“…4,10 Swine confinement buildings that are equipped with systems that separate solid and liquid manure have better air quality than conventional systems without such separation. 9 Workers who manually feed nursery pigs suffer from high exposure to airborne bacteria, odors, and H 2 S. 3,[11][12][13] Similarly, the size distribution and concentrations of particulates in swine buildings are affected by the degree of animal activity, ventilation, bedding materials, and floor type. 12, 13 Oppliger and co-workers 2 demonstrated that occupational exposure to inhalable dusts, endotoxins, and bacteria is related to the growth stage of the animals because the biomass of feces and feather dandruff increase drastically during fattening periods.…”
Section: Introductionmentioning
confidence: 99%